Toward Engineered Nanoparticle-Doped Optical Fibers for Sensor Applications - Lu, Zhuorui; Robine , Thibaut; Molardi, Carlo; Pigeonneau, Franck; Tosi, Daniele; Blanc, Wilfried (Frontiers in Sensors, 2022)
Nanoparticles-doped optical fibers, investigated first as fiber lasers and fiber amplifiers, have gained a tremendous interest over the past few years as fiber sensors. One of the main interest of such fibers relies on the ability to develop a distributed sensor allowing to measure in real-time with a multiplexed architecture. To go above the actual proof-of-concept, we discuss in this perspective paper on three main challenges to tackle: understanding light propagation in heterogeneous material, controlling nanoparticles formation in glass, engineering nanoparticles characteristics. Identified as the main directions to follow, they will contribute to promote nanoparticles-doped fiber sensors in the next few years.